Quality and cost of healthcare services in patients with diabetes in Iran: Results of a nationwide short-term longitudinal survey - Abbasi-Kangevari, Mohsen; Mohebi, Farnam; Ghamari, Seyyed-Hadi; Modirian, Mitra; Shahbal, Nazila; Ahmadi, Naser; Farzi, Yosef; Azmin, Mehrdad; Roshani, Shahin; Zokaei, Hossein; Khezrian, Maryam; Seyfi, Shahedeh; et al. (Frontiers in Endocrinology, 2023)
Aims To investigate the journey of patients with diabetes in the healthcare system using nationally-representative patient-reported data. Methods Participants were recruited using a machine-learning-based sampling method based on healthcare structures and medical outcome data and were followed up for three months. We assessed the resource utilization, direct/indirect costs, and quality of healthcare services. Results One hundred fifty-eight patients with diabetes participated. The most utilized services were medication purchases (276 times monthly) and outpatient visits (231 times monthly). During the previous year, 90% of respondents had a laboratory fasting blood glucose assessment; however, less than 70% reported a quarterly follow-up physician visit. Only 43% had been asked about any hypoglycemia episodes by their physician. Less than 45% of respondents had been trained for hypoglycemia self-management. The annual average health-related direct cost of a patient with diabetes was 769 USD. The average out-of-pocket share of direct costs was 601 USD (78.15%). Medication purchases, inpatient services, and outpatient services summed up 79.77% of direct costs with a mean of 613 USD. Conclusion Healthcare services focused solely on glycemic control and the continuity of services for diabetes control was insufficient. Medication purchases, and inpatient and outpatient services imposed the most out-of-pocket costs.